Application of Herbal Exudates in Traditional Persian Medicine: - Zargaran, Arman; Zarshenas, Mohammad M.; Arabzadeh, Atefeh; Ajdari Tafti, Mehdi; Kordafshari, Gholamreza; Mohagheghzadeh, Abdolali (Galen Medical Journal, 2013)
Introduction: Traditional Persian medical and pharmaceutical manuscripts authored by medieval Persian scholars offer not only accumulation of traditional medical systems knowledge, but also contain collection of ingenious studies that provide vast information in the field of medicinal herbs application. One of the most cited derivative compositions of medicinal herbs are exudates. A large group of these compounds along with their different clinical and pharmacological applications can be found in the manuscripts of Persian medicine. Methods and Materials: This work is a literature research on some main traditional manuscripts of Persian medicine, including the book of Alhavi, Canon of Medicine, the book of Tohfat ol Moemenin, and Makhzan ol advieh. Also, current investigations on related subjects were considered by searching in Medline/PubMed and Google Scholar databases. Results: According to the investigated manuscripts, thirty-one substances, incorporating plant exudates relating to sixteen plant families, were used to combat simple to sophisticated ailments. Mostly exudates were derived from herbs of family, Asteraceae, Apiaceae with six and five citations, respectively. Other than the reported clinical applications for herbs, which were defined as a source for gummy compositions, numerous pharmacological approaches were also remarked for the secreted gums. Conclusion: Application of ethnobotanical findings on simple remedies offers rational criteria to evaluate the potential therapeutic properties of medicinal plants.[GMJ. 2012;1(2):78-83]